ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII SMP NEGERI 13 PADANG DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN ANALISIS KESALAHAN NEWMAN - Aisya Wina (Departemen Matematika, 2022)
The purpose on this research is to explain and analyze errors made by students in class VIII at SMP Negeri 13 Padang when solving math problems involving the Pythagorean Theorem using Newman's Error Analysis. According to the findings, students make following mistakes when answering math questions about the Pythagorean Theorem: (a) reading errors include errors in reading useful data in the problem with an error percentage rate of 18,4%; (b) misunderstanding the question isn’t writing down what has known and asked is accordance wih question request with an error percentage rate of 19,02%; (c) problem transformation error where cannot ensure the right strategy or formula to use in solving problems with an errors rate of 22,09%; (d) process skill error isn’t applying the calculation operation, applying the calculation but the results is wrong with the error percentage rate of 19,02%; (e) errors in compiling final answer where isn’t writing this final answer, not writing the unit with a percentage error rate of 21,47% which is the problem transformation error percent rate the largest tase among the other four errors. The factors that cause students to made mistakes were low attention, motivation and student behavior in learning mathematics, the lack of understood of the information contained in the questions, less skilled in using formulas and arithmetic operations, not mastering the prerequisite materials needed to answer these questions, don’t study seriously when the teacher is explaining and teaching, lack of practice questions with different levels of difficulty and variations of questions. Keywords – Mathematical Problems, Error Analysis, Newman’s Analysis